A Multiple Lines of Evidence Framework to Evaluate Intrinsic Biodegradation of 1, 4‐Dioxane. Issue 1 (5th December 2016) - Gedalanga, Phillip; Madison, Andrew; Miao, Yu (Rain); Richards, Timothy; Hatton, James; DiGuiseppi, William H.; Wilson, John; Mahendra, Shaily
Abstract : Development of a multiple lines of evidence (MLOE) framework to evaluate the intrinsic biodegradation potential of 1, 4‐dioxane is vital to implementing management strategies at groundwater sites impacted by 1, 4‐dioxane. A comprehensive MLOE approach was formed to provide significant evidence of natural degradation of 1, 4‐dioxane comingled with tetrahydrofuran (THF) within a large, diffuse plume. State‐of‐the art molecular biological analyses and compound‐specific isotope analysis (CSIA) were employed to support more traditional approaches for data analysis (concentration trend analyses, spatial distribution, temporal changes, geochemical biodegradation attenuation indicators, plume mass estimates, and fate and transport modeling). The molecular analyses demonstrated that microorganisms capable of both metabolic and cometabolic degradation of 1, 4‐dioxane were present throughout the groundwater plume, whereas the CSIA data provided supporting evidence of biodegradation. 1, 4‐Dioxane biomarkers were present and abundant throughout the 1, 4‐dioxane plume, and our biomarkers tracked the plume with reasonable accuracy. Evidence also suggests that THF‐driven cometabolic biodegradation as well as catabolic 1, 4‐dioxane biodegradation were active at this site. These data supplemented the traditional lines of evidence approaches, which demonstrated that 1, 4‐dioxane attenuation was occurring across the groundwater plume and that nondestructive physical processes alone did not account for the observed 1, 4‐dioxane attenuation. This MLOE framework combining new and traditional analyses demonstrates that this site has a significant capacity for intrinsic biodegradation of 1, 4‐dioxane. ©2016 Wiley Periodicals, Inc.